Genomic adaptation in antimicrobial resistance: Elucidating the route and effects in acinetobacter baumannii / Mohamad Izwan Ismail - Ismail, Mohamad Izwan (Institute of Graduate Studies, UiTM, 2016)
Antimicrobial resistance has been a looming threat ever since its conception and it has become one of the greatest global problems of the current era. Although various studies have been conducted to better understand the mutational triggers leading to antimicrobial resistance, the specific genomic path towards it have yet to be discerned. Here, we aim to elucidate the pathway of genomic evolution throughout the resistance induction of an A. baumannii strain towards ciprofloxacin, erythromycin, meropenem and imipenem, as well as comparing the mutations acquired clinically versus in vitro. Twenty-five (25) local clinical A. baumannii strains were isolated and screened for antimicrobial susceptibility, and their genome were sequenced using the Illumina GAIIx genome sequencer. The susceptible parent was then challenged with ciprofloxacin, erythromycin, meropenem and imipenem separately until growth is still possible beyond the Minimum Inhibitory Concentration (MIC) as defined by EUCAST standards. Once the resistance stability was confirmed, another sequencing run was done on the isogenic. Variant analysis was carried out using CLC Bio, and primers were designed to target the mutations of interest. PCR was then carried out on aliquots of the resistant mutants, each taken at increasing levels of antimicrobial tolerance throughout the challenging process. Phylogenomics and wgMLST analyses were carried out between the parent and resistant strain, as also the remaining isolates. Stable low and high-level resistant strains were successfully generated. Several genomic variants were identified in the high-level resistant strains…